Estimation of economic values in three breeding perspectives for longevity and milk production traits in Holstein dairy cattle in Iran - Abdolahad Shadparvar; Ardeshir Nejati-Javaremi; Mohammad Moradi-Shahrbabak; Ali Ali Sadeghi-Sefidmazgi (Italian Journal of Animal Science, 2010)
The objectives of this study were to estimate economic values (EVs) for three production traits (milk, fat and protein yields) and longevity and to develop a national selection index. The proposed Iranian selection index was compared with selection indices of three other countries in the world. A simple and appropriate model was used to describe the Holstein dairy cattle industry under an Iranian production system. Production parameters and economic data were collected from two Holstein dairy farms in Tehran province. The EVs were estimated at farm level for three breeding perspectives (maximized profit, minimized costs, and economic efficiency) and two restrictions in production system (fixed herd size and fixed total input). The average absolute EVs on profit perspective and herd size restriction for milk, fat, and protein yields (based on $/kg) and longevity ($/month) were 0.11, 0.89, -0.20, and 6.20, respectively. The average absolute EVs under minimized costs per unit of product interest for milk, fat, protein yields and longevity were -0.30, -3.43, 0.88 and -20.40, respectively. The average absolute EVs under maximized economic efficiency for milk, fat and protein yields and longevity were 0.34, 2.73, -0.99 and 36.33, respectively. Relative emphasis for three production traits and longevity were 59.7, 14.3, -3.0 and 23.1, respectively. The comparison of the proposed Iranian index with those countries where most of the semen and embryos are imported points out that developing a national selection index to improve cow profitability and optimum generic trends is necessary. Sensitivity analysis indicated that the influence of milk payment changes on EVs was the greatest as its influence on fat and protein EVs is substantial. EVs for milk and fat yields, with respect to price changes (milk, feed and non-feed), were the least sensitive and most sensitive, respectively.